2016
DOI: 10.1136/bjsports-2015-h2469rep
|View full text |Cite
|
Sign up to set email alerts
|

Peer victimisation during adolescence and its impact on depression in early adulthood: prospective cohort study in the United Kingdom

Abstract: PartiCiPants 6719 participants who reported on peer victimisation at age 13 years. Main OutCOMe MeasuresDepression defined according to international classification of diseases, 10th revision (ICD-10) criteria, assessed using the clinical interview schedule-revised during clinic assessments with participants when they were aged 18 years. 3898 participants had data on both victimisation by peers at age 13 years and depression at age 18 years. resultsOf the 683 participants who reported frequent victimisation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
17
0
2
Order By: Relevance
“…Depressive symptoms were assessed using the Clinical Interview Schedule-Revised (CIS-R; Lewis, 1994;Lewis, Pelosi, Araya, & Dunn, 1992), which was self-administered via a computerized questionnaire during the 18-year clinic visit (Bowes, Joinson, Wolke, & Lewis, 2015).…”
Section: Depression Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressive symptoms were assessed using the Clinical Interview Schedule-Revised (CIS-R; Lewis, 1994;Lewis, Pelosi, Araya, & Dunn, 1992), which was self-administered via a computerized questionnaire during the 18-year clinic visit (Bowes, Joinson, Wolke, & Lewis, 2015).…”
Section: Depression Outcomesmentioning
confidence: 99%
“…We, therefore, conducted multiple imputations of missing data using fully conditional specification implemented in SAS (version 9.4; SAS Institute Inc., Cary, NC). This method uses an iterative approach to imputation that can flexibly accommodate different variable distributions (Berglund, 2015;van Buuren, 2007) and has been used in several previous studies of the ALSPAC cohort with similar amounts of missing information (Bowes et al, 2015;Culpin, Stapinski, Miles, Araya, & Joinson, 2015;Hammerton et al, 2015;Stapinski et al, 2014). The imputed sample were those with data for at least four of the eight adversity time points from birth through age 11.5 years (n = 9,665; Figure 1); this sample was highly similar to the larger base sample (eTable S3).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Bullying victimization is a common social determinant of health among adolescents, with 8% of 15 year olds surveyed in 37 countries reporting at least two episodes of bullying victimization in the previous "few" months (WHO, 2014). Research has shown that bullying victims have a significantly greater risk of depression (Bowes, Joinson, Wolke, & Lewis, 2016), suicide (Bauman et al, 2013;Messias et al, 2014;Mueller et al, 2015;Sibold et al, 2015;Van Geel et al, 2014), substance use (Valdebenito, Ttofi, & Eisner, 2015), sexual risk-taking (Hertz, Everett, Barrios, David-Ferdon, & Holt, 2015), school avoidance (Hutzell & Payne, 2017) and other psychological and behavioral problems (Litwiller & Brausch, 2013;Olweus, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bullying among children and adolescents is a worldwide phenomenon, often associated with adverse effects on students' mental health, 1,2 school absenteeism, 3 and poor academic achievement. 4,5 In addition to short-term effects, bullying has numerous undesirable long-term behavioral consequences for victims, such as depression, anxiety, self-mutilation, [6][7][8][9][10] suicide, or suicide attempts. 11,12 Even though the term bullying tends to be used in the media as a blanket term that encompasses aggressive or negative acts among individuals, social-scientific studies over the past few decades have focused on how bullying should be defined.…”
mentioning
confidence: 99%